2019
DOI: 10.1370/afm.2379
|View full text |Cite
|
Sign up to set email alerts
|

Connecting People With Multimorbidity to Interprofessional Teams Using Telemedicine

Abstract: PURPOSE Most models for managing chronic disease focus on single diseases. Managing patients with multimorbidity is an increasing challenge in family medicine. We evaluated the feasibility of a novel approach to caring for patients with multimorbidity, performing a case study of TIP-Telemedicine IMPACT (Interprofessional Model of Practice for Aging and Complex Treatments) Plus-a 1-time interprofessional consultation with primary care physicians (PCPs) and their patients in Toronto, Canada. METHODSWe assessed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 31 publications
0
34
0
1
Order By: Relevance
“…Video consultations have been found to support patients with chronic conditions and prevent unnecessary admissions to long-term institutional care [ 29 ]. In Canada, they have made possible an interprofessional model of practice involving hospital specialists, a social worker, a pharmacist, a home care community coordinator, and other allied health professionals who allow older patients with complex multimorbidity to be managed within the community [ 30 ]. Jiwa et al [ 31 ] reported that Australian general practitioners who were favorably inclined toward video consultations were more likely to work in larger practices and be more established professionally.…”
Section: Discussionmentioning
confidence: 99%
“…Video consultations have been found to support patients with chronic conditions and prevent unnecessary admissions to long-term institutional care [ 29 ]. In Canada, they have made possible an interprofessional model of practice involving hospital specialists, a social worker, a pharmacist, a home care community coordinator, and other allied health professionals who allow older patients with complex multimorbidity to be managed within the community [ 30 ]. Jiwa et al [ 31 ] reported that Australian general practitioners who were favorably inclined toward video consultations were more likely to work in larger practices and be more established professionally.…”
Section: Discussionmentioning
confidence: 99%
“…By addressing the holistic needs of patients with multimorbidity, eHealth (i.e. information and communication technologies used to facilitate health promotion and care) has the potential to help promote patient-centered care, and thus, self-management [26,27]. However, both patients and professionals have been reluctant to adopt eHealth tools [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Some institutions may also need to incorporate allied health providers or health educators at the start, middle or end of the visit. Yet other departments may have a multi-disciplinary team providing consultation simultaneously (Pariser et al 2019;O'Hara et al 2020). The location of team members and how they will communicate with each other also needs to be determined, for example, via video conferencing or phone call.…”
Section: Develop a Functional Workflowmentioning
confidence: 99%
“…technology literacy, lack of internet) that may limit the effectiveness of telemedicine and reduce its adoption. Telemedicine offers a breadth of opportunity for rethinking how health care teams interact to facilitate patient care; therefore, they should receive instruction on potential opportunities for incorporating other healthcare professionals (Huang et al 2019;Pariser et al 2019;O'Hara et al 2020). Ultimately, this curriculum should be informed by the literature and align with already established professional training standards.…”
Section: Tipmentioning
confidence: 99%